2020
DOI: 10.3390/en13061410
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Adaptive Joint Estimation of the State of Charge and Capacity for Lithium–Ion Batteries in Their Entire Lifespan

Abstract: In this paper, a co-estimation scheme of the state of charge (SOC) and available capacity is proposed for lithium-ion batteries based on the adaptive model-based algorithm. A three-dimensional response surface (TDRS) in terms of the open circuit voltage, the SOC and the available capacity in the scope of whole lifespan, is constructed to describe the capacity attenuation, and the battery available capacity is identified by a genetic algorithm (GA), together with the parameters related to SOC. The square root c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…When the environment around the carrier changes, its statistical characteristics change greatly together with the observation noise of the carrier. Meanwhile, the prediction accuracy and stability are reduced greatly and the error covariance is updated, as shown in Equation (12).…”
Section: Iterative Prediction and Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the environment around the carrier changes, its statistical characteristics change greatly together with the observation noise of the carrier. Meanwhile, the prediction accuracy and stability are reduced greatly and the error covariance is updated, as shown in Equation (12).…”
Section: Iterative Prediction and Correctionmentioning
confidence: 99%
“…To realize the accurate available energy prediction, observing strategies are introduced into the iterative calculation process, such as Adaptive Dual Kalman Filtering, Thermoelectric Coupling Modeling, and Open-Circuit Voltage (OCV). [9][10][11][12] In the calculation process, the effective energy state prediction can be realized by combining the experimental data. By conducting the State of Balance prediction for lithium-ion battery packs, the onboard dynamic balancing adjustment of the battery pack is carried out to improve its power supply performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on effective electrical models such as equivalent circuit model (ECM), a number of advanced filter algorithms (such as Kalman filter (KF) and PF) can then be adopted to conduct the joint estimation of battery status and model parameters [13]. In [14], a second-order resistancecapacitance (RC) ECM is established, and the square root cubature KF is employed to estimate the SOC. Meanwhile, the capacity, as one of the key parameters of model, is identified by the genetic algorithm (GA).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 At present, a lot of researchers have made numerous studies on the SOC estimation of Li-ion batteries and suggested various approaches to estimate SOC. [18][19][20] A model-based SOC estimation approaches are most widely employed, including extended Kalman filter (EKF), unscented Kalman filter (UKF), and cubature Kalman filter (CKF). 21,22 EKF has large calculations and weak stability due to its Jacobian matrix of nonlinear model, which constrains its application scope.…”
mentioning
confidence: 99%